Role of serum asymmetric dimethylarginine level in cardiovascular diseases early prognostic in patients with obstructive sleep apnea-hypopnea syndrome - Wang, Jinping; Yuan, Lijie; Zhang, Haixiang; Yun, Yonggang (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this paper was to investigate the role of serum asymmetric dimethylarginine (ADMA) in patients with obstructive sleep apnea-hypopnea syndrome (OSAHS) and identify its clinical significance in OSAHS related cardiovascular diseases. A total of 75 patients with OSAHS were enrolled and divided into mild (n=25), moderate (n=27), and severe group (n=23) according to their apnea hypopnea index (AHI) and minimal oxygen saturation (SaO2 min), respectively. Thirty healthy individuals were enrolled as normal control. Serum ADMA was measured with enzyme-linked immunosorbent assay (ELISA). Nitric oxide (NO) level was assayed with colorimetric method. Nasal continuous positive airway pressure (nCPAP) treatment was performed to the patients, and the follow up lasted for 2 months. Serum ADMA level increased with the severity of patients. Serum NO level decreased with severity of patients. A negative correlation was noticed between serum NO and mean SaO2 (SaO2 mean) and minimal SaO2 (SaO2 min). Serum ADMA was positively correlated with AHI, tSaO2<90%, and morbidity of cardiovascular diseases. After nCPAP therapy, the serum ADMA level was remarkably decreased and NO was remarkably increased in patients with OSAHS. Serum ADMA may be correlated with OSAHS and OSAHS related cardiovascular diseases. Reducing the plasma ADMA level by nCPAP therapy can reduce the morbidity of OSAHS-related cardiovascular diseases.